Awareness Level of Traffic in the Mukomuko Regency: Awareness Level of Traffic in the Mukomuko Regency - Mahdi, Sutiono (International Journal of Humanities, Law, and Politics, 2023)
The problem is even though law enforcement management of motor vehicle violations in Mukomuko Regency already exists based on Law Number 22 of 2009 concerning Road Traffic and Transportation, the level of public awareness of traffic in Mukomuko Regency is still not effective. However, there are still signs of an irresponsible person, such as a driver who constantly violates traffic rules. This is the result of the habit of people who are not allowed to ride motorbikes. This study aims to measure public knowledge about traffic problems and identify challenges faced by law enforcement. In order to create a thorough and accurate picture of the problem under investigation, sociological legal research is the type of research used. This is because this type of research is carried out directly at the location or place under study. All parties involved in the problem under study became the sample population for this study which was conducted in Mukomuko Regency. Primary, secondary, and terser sources of information were used. In this research, data collection methods are observation, interviews, and literature review. From this research, it is possible to draw conclusions on a number of fundamental issues. First, depending on traffic laws and regulations there is relatively little public understanding of traffic in Mukomuko Regency. Secondly, based on Article 77, Paragraph 1, of Law Number 22 of 2009 Concerning Road Traffic and Transportation, the challenges that the Police must overcome in order to raise public awareness of traffic. The police must contend with motorists that disobey and break traffic laws.